Outdoor Walking Training Compared To Cycle Ergometer Training in Severe COPD: A Randomized Controlled Feasibility Trial. (2nd January 2019) - Gamper, Esther; Schmidt, Ulrich; Bansi, Jens; Kool, Jan
Abstract: Exercise can improve walking capacity in persons with chronic obstructive pulmonary disease (COPD). However, most endurance training programs use cycle ergometers. The objectives of this study were: (i) to evaluate the feasibility of a randomized controlled trial (RCT) comparing outdoor walking training (OWT) to cycle ergometer training (CT) during inpatient rehabilitation in persons with severe COPD; (ii) to estimate the effect of OWT and CT on health-related quality of life, physical capacity and physical activity; and (iii) to estimate the required sample size for a RCT. A single-blind randomized controlled feasibility trial was conducted with three months' follow-up in the rehabilitation center in Walenstadtberg, Switzerland. Sixteen patients were included in the study, which had a recruitment rate of 33% (16/48). Patients were allocated to an OWT ( n  = 8) or CT ( n  = 8) group. Participants completed 75% of scheduled training and the follow-up rate was 75%. All participants in the OWT group were satisfied with the training. The OWT group had better health-related quality of life after three weeks' training compared to the CT group ( p  = 0.042, 95% confidence interval (95% CI) 1.06–49.94, effect size ( d )=1.19). No exacerbations occurred in the OWT group, but three occurred in the CT group after three months' follow-up. There was no significant difference in the other outcomes. In conclusion, the study design and the OWT are feasible. Health-related quality of life improved in the OWT group compared to the CT group after three weeks' inpatient rehabilitation. A minimum of 46 participants is needed for a RCT. Trial registration: www.who.int/trialsearch DRKS00010977